Evaluación de un proceso de inyección de polímero mediante simulación numérica considerando diferentes fuentes de agua de inyección y su impacto técnico-económico para el campo Yarigui-Cantagallo (2020)
This project evaluated the behavior of partially hydrolyzed polyacrylamide polymer (HPAM) in different water sources for an injection process by means of a conceptual numerical simulation, in the YR-504 well of Campo Yariguí-Cantagallo, evaluating the technical-economic impact of this recovery process enhanced with the Net Present Value financial indicator, taking into account investment cost and operational costs. The Yariguí-Cantagallo field describes its location, the production history and the pilot's commissioning process. For the polymer injection process, the behavior of partially hydrolyzed polyacrylamide (HPAM) was evaluated by laboratory testing, from the generation of mother solutions in different water sources, considering the API RP standard 63. For the execution of the tests, 5 samples were taken from each source varying the concentration of the polymer.